Engineering Education-Some Thoughts - Agrwal, Jyoti R. (Journal of Engineering Education Transformations, 1994)
The output by an engineer or for that matter by any professional depends on many factors. The important one is quality of education provided to the student. The student, to receive the quality education should also be compatible with the inputs being provided. This paper aims at presenting an outline guidelines for the engineering education in India. It discusses the various sub-systems in engineering education to greater length.